THE ROLE OF ERGONOMICS IN WORKSTATION MANAGEMENT TO IMPROVE PRACTICAL PERFORMANCE OF SMK NEGERI 1 SINGOSARI STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Arif, Mukhamad; Hutabarat, Julianus; Vitasari, Prima (Journal of Industrial Engineering Management, 2025)
This study aims to systematically review literature related to the role of ergonomics in workstation management to improve practical performance among students at SMK Negeri 1 Singosari. The systematic literature review method was utilized, involving the identification, evaluation, and synthesis of scholarly articles published between 2014 and 2024. Searches were conducted in reputable databases including Google Scholar, Scopus, ScienceDirect, SpringerLink, IEEE Xplore, and PubMed, using relevant keywords such as ergonomics, workstation management, vocational education, and student performance. Rigorous inclusion and exclusion criteria guided the selection of articles to ensure relevance, quality, and credibility. Analysis was performed thematically, categorizing findings into physical, cognitive, and organizational ergonomic factors. The results indicated that effective ergonomic practices significantly enhanced student comfort, concentration, safety, and productivity during practical learning activities. Supporting factors identified included adequate funding, administrative support, and increased ergonomic awareness, whereas barriers encompassed financial limitations, inadequate facilities, and resistance to change. This study underscores the importance of adopting ergonomically optimized environments to foster practical skill mastery and increased student motivation. Recommendations are provided for SMK Negeri 1 Singosari to integrate ergonomics more systematically, including curriculum-based ergonomic training, establishing ergonomic oversight committees, and fostering strategic collaborations to enhance student outcomes comprehensively